A distinctive new species of biting midge in the subgenus Euprojoannisia Brèthes from Mexico with new records of Neotropical species of Forcipomyia Meigen (Diptera: Ceratopogonidae) - Huerta, Heron; Spinelli, Gustavo R. (Zootaxa, 2017)
A new species of biting midge, Forcipomyia (Euprojoannisia) bibaana, is described and illustrated from an adult male collected in the state Oaxaca, Mexico. The first records of Forcipomyia (E.) mortuifolii Saunders, F. (Lasiohelea) cornuta Saunders and F. (L.) stylifer (Lutz) are provided from Mexico as well as the first record of F. (L.) anitae Huerta & Ibáñez-Bernal from Guatemala.